Cultura e território da imigração polonesa no município de Áurea/RS - Socoloski, Thaimon da Silva (2018)
The European immigration to the south of Brazil became one of the main migratory flows in the colonization process as well as in the agricultural development aimed by the Brazilian state. Considering this migratory flow, the Polish immigration was important to Rio Grande do Sul and, primarily, as the main focus in this study, the colonization of Áurea, starting in 1911. This research aims at analyzing and showing the main cultural codes inherited by the immigrants‟ descendants that survive as a living part of the Polish tradition memory. The main purpose is to discuss the importance of this migratory process to the cultural elements which appear in the routine of these Polish descendants who currently live in Áurea. Besides this, the study involves: a) examining the process of desterritorialization and reterritorialization by the Polish immigrants in Rio Grande do Sul; b) evaluating the relevance of these Polish immigrants to the development of Áurea/RS; c) identifying and describing the Polish cultural codes and their representations in the city according to the Polish identity. Methodologically, field research as well as documental and observatory analysis were used, combined with the exploratory research based on the examination of pre-determined sources, such as bibliography data, interviews with people who have had practical experiences with the research problem and the analysis of examples to stimulate the comprehension. Then, the following cultural codes were analyzed: religion, language and dialect, arts, dance, music, cuisine, architecture and costume. It was possible to observe that for decades and since the new generations, after more than one century of colonization, most of these codes are still alive in the traditions and the descendants‟ daily habits, their religious ceremonies, the dialect and the cuisine. However, the process of new culture assimilation in Brazil has become more latent and it is replacing the tradition which survived and has been surviving among the generations closer to the immigrants. Finally, the valorization and the perpetuation of the immigrants‟ heritage and memories have been kept, from generation to generation, and this process is crucial to avoid neither losing nor forgetting the history of Áurea.